Estimation of D-dimer, C-reactive protein and ferritin in Covid-19 survivors in a North Indian Hospital, Lucknow, India. - Chetna Singla; Dhananjay Tiwari; Himali Jha; Mohammad Mustufa Khan; Sadaf Parveen; Roshan Alam (Indonesian Society for Biochemistry and Molecular Biology, 2023)
Background: Novel coronavirus disease (COVID-19), the disease caused by SARS-CoV-2, is a highly contagious disease. COVID-19 caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which was initially thought to affect only the upper respiratory tract, can affect almost all systems. COVID-19 survivors who are critically ill featured hyper inflammation and the associated biomarkers may be useful for risk stratification. Objective: We aimed to estimate the levels of several biomarkers, including serum C-reactive protein (CRP), D-dimer, and serum ferritin in Covid-19 survivors to reduce the further disease complication and its-associated mortality. Method: This case-control study was conducted on COVID-19 survivors and a control group without a history of Covid-19. The D-dimer and Ferritin were determined by using Mini Vidas Immuno assay analyser and CRP was estimated Dimension RXL Siemens autoanalyzer by Particle Enhanced Turbidimetric Immunoassay. Results: The results indicated that CRP levels were higher in COVID-19 survivors compared to controls (p<0.0001). The mean of D-dimer was found to be elevated in COVID-19 survivors as compared to controls (p<0.0001). Similarly, the ferritin level was also found to be raised in COVID-19 survivors as compared to controls (p<0.0001). Conclusion: Results revealed that COVID-19 survivors had considerably higher mean levels of CRP, D-dimer, and ferritin than controls.